Ethanolic Extract of The Graptophyllum Pictum Griff Leaves to Male White Rat - Setya Enti Rikomah; Gina Lestrari; Juwita Winanti (Denta Journal Kedokteran Gigi, 2018)
Utilization of plants as traditional medicinal are still always be used by people in Indonesian. Especially in rural areas that still rich with variety of plants. Plants of black pudding leaves (Graptophyllum pictum Griff) are one that efficacious for treating various of diseases. The content of flavonoid in the black pudding leaves have antipyretic effect, analgesic and anti-inflammatory. This research aims to find out whether the black pudding leaves have antipyretic effect or not. This research used the induction method of vaccineDPT-Hb 0.022 / 20 gr a white rat as stimulant fever. Positive control with paracetamol 1.3 mg / 20 gram a white rat, negative control with Na CMC 0.5 ml / 20 grams a white rat, first extract test of black pudding leaves 0.8 mg / 20 gram a white rat, second extract test of black pudding leaves 1.6 / 20 gram a white rat, and third extract test of black pudding leaves 3.2 / 20 gram a white rat. The results of research showed that ethanol extract of black pudding leaves if it’s looked from statistic result of SPSS 16 program , it doesn’t show out of any effect as antipyretic effect because the significant value is P> 0.05.